Common Bunt Resistance of Winter Wheat Genotypes Under Artificial Infection - Tagayev, Kuttymurat; Morgounov, Aleksey; Yessimbekova, Minura; Abugalieya, Aigul (International Journal of Engineering and Technology, 2018)
Common bunt (Tilletia caries) is a seed-transmitted fungal disease in wheat. The resistant cultivars and germplasm lines of wheat will be useful for control this type of disease in organic farming. A set of 75 wheat cultivars and lines from International Winter Wheat Improvement Program (IWWIP) of Turkey were used to determine resistance to common bunt. The experiment was carried out at the Kazakh Research Institute of Agriculture and experimental material was grown in an artificially inoculated nursery during the 2016-2017 season. The productivity of wheat genotypes under artificial infection ranged from 1.13 t/ha to 7.29 t/ha. The susceptible check to common bunt, GEREK 79 had a high level of susceptibility to common bunt with 59.7% infected heads. The high mean disease incidence in the nursery was 74.4%. Sixteen genotypes were resistant to disease under artificial inoculation. Out of 75 wheat cutivars, 42 wheat genotypes (56% of all genotypes) were classified as moderate resistance to disease. Identified resistance genotypes will be useful for breeding programs for forming resistance cultivars to common bunt in Kazakhstan.Â Â Â
Keywords: Common bunt; Productivity; Resistance; Wheat; Wheat cultivars; Wheat lines.